Medicinal Properties And Agrotechnology Of Cultivation Of Capparis Herbacea Willd - Gulnara J. Abdiniyazova; Baxieva L.A (Zien Journals, 2025)
The article provides information about the distribution, life cycle, medicinal properties, uses, and agricultural technology of the marigold plant. The plant is a first-class honey-juicing plant. Its flowers contain a large amount of nectar. A large flower of the thorny thorn yields one drop of honey, while one bush yields 3,000 drops of honey during the season. In addition to its medicinal uses, the root is also used to obtain natural dyes. Since ancient times, pickles have been prepared and consumed from the buds of the thorny thorny thorn. During agrotechnical activities, in July-November, the ripened fruits of the plant are picked and the seeds are separated. 100 gr from a bush of perennial sorghum. until the seed is taken
Keywords: medicinal plants; perennial creeping; above-ground part